2004
DOI: 10.1159/000079826
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Metabolism of <i>Lactobacillus rhamnosus</i> ATCC 7469: Cloning and Expression of Two Glycerol Kinase Genes

Abstract: Lactobacillus rhamnosus ATCC 7469 was able to grow in glycerol as the sole source of energy in aerobic conditions, producing lactate, acetate, and diacetyl. A biphasic growth was observed in the presence of glucose. In this condition, glycerol consumption began after glucose was exhausted from the culture medium. Glycerol kinase activity was detected in L. rhamnosus ATCC 7469, a characteristic of microorganisms which catabolize glycerol in aerobic conditions. Genetic analysis revealed that this strain possesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…DHAP is an intermediate in glycerol metabolism and was found to increase by 3.3-fold in MOM samples (p < 0.001). It has been reported that several bacterial species found in milk, including Lactobacillus plantarum, L. delbrueckii, L. acidophilus, L. rhamnosus, and Enterococcus faecalis, are able to catabolize glycerol into DHAP through their metabolism [48,49]. It has also been reported that gut microbiota can use choline as a precursor to produce phosphatidylcholine [50,51].…”
Section: Milk Personalization Results In Global Shifts In the Metabolmentioning
confidence: 99%
“…DHAP is an intermediate in glycerol metabolism and was found to increase by 3.3-fold in MOM samples (p < 0.001). It has been reported that several bacterial species found in milk, including Lactobacillus plantarum, L. delbrueckii, L. acidophilus, L. rhamnosus, and Enterococcus faecalis, are able to catabolize glycerol into DHAP through their metabolism [48,49]. It has also been reported that gut microbiota can use choline as a precursor to produce phosphatidylcholine [50,51].…”
Section: Milk Personalization Results In Global Shifts In the Metabolmentioning
confidence: 99%
“…H. volcanii (and some other haloarchaea) (Rawls et al, 2011;Williams et al, 2017). The presence of two GK paralogues appears even more unusual and has been described so far for Lactobacillus rhamnosus and Pseudomonas aeruginosa (de Fátima Alvarez et al, 2004;Tang et al, 2023). In the archaeal domain, also few haloarchaea were found to harbor two GK copies (Williams et al, 2017).…”
Section: Only Saci_2033 Gk Is Essential For Glycerol Degradationmentioning
confidence: 76%
“…The quantification of H 2 O 2 production by S. pluranimalium 2N12 was assessed using the LAPTg medium described by Alvarez et al ( 14 ). LAPTg medium contains 1.5% (w/v) peptone, 1% (w/v) tryptone, 1% (w/v) yeast extract, 1% (w/v) glucose, and 0.1% (v/v) Tween 80.…”
Section: Methodsmentioning
confidence: 99%